Calcium/calmodulin-dependent protein kinase II α and β differentially regulate mammalian sleep - Weiwen Yang; Jingyi Shi; Chenggang Li; Jingqun Yang; Jianjun Yu; Juan Huang; Yi Rao (Communications Biology)
Abstract While sleep is important, our understanding of its molecular mechanisms is limited. Over the last two decades, protein kinases including Ca2+/calmodulin-dependent protein kinase II (CaMKII) α and β have been implicated in sleep regulation. Of all the known mouse genetic mutants, the biggest changes in sleep is reported to be observed in adult mice with sgRNAs for Camk2b injected into their embryos: sleep is reduced by approximately 120 min (mins) over 24 h (hrs). We have reexamined the sleep phenotype in mice with either Camk2a or Camk2b gene knocked-out by conventional gene targetting. While the basal sleep is reduced in Camk2a knockout mice, it remains unaltered in Camk2b mutants. Knockout of either Camk2a or Camk2b reduces sleep rebound after deprivation, indicating their roles in sleep homeostasis. These results indicate the involvement of CaMKIIα in both basal sleep and sleep homeostasis while CaMKIIβ is mainly required physiologically for sleep homeostasis, serving as a stimulus for rigorous studies in the future.